The Importance of Play in the Activities of Preschool Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is known that play is an integral part of children's development. Effective organization of games in preschool educational institutions not only increases the child’s interest in activities, but also has a great impact on his mental and physical development. In this sense, the role of the teacher in choosing the correct way to organize the game, the type of game and teaching the child to play correctly is incomparable. This article is about them.